Interface-enhanced environment-friendly artificial stone and preparation method thereof

By performing intermittent grading and mineralization of artificial stone aggregates, combining inorganic gelling materials and organic cementitious materials, interface-enhanced environmentally friendly artificial stones are prepared, which solves the problem of particle shedding on the surface of artificial stones and improves strength and performance. It has environmental and economic advantages.

CN119462019APending Publication Date: 2025-02-18CHINA STATE CONSTR HAILONG TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411661087.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, particles are shed on the surface of artificial stone, resulting in depressions and potholes, affecting performance.

Method used

By performing interrupted grading of aggregates, mineralized aggregates with particle sizes between 1.18mm and 2.36mm are eliminated, and the bonding force between aggregate particles is increased. The mineralized bone obtained by mineralization treatment is used for waste cement concrete. In addition, inorganic gelling materials, organic cementing materials, etc. are used to prepare interface-enhanced environmentally friendly artificial stones.

Benefits of technology

It effectively reduces the phenomenon of particles falling off on the surface of artificial stone, enhances the adhesion between aggregate particles, improves the strength and performance of artificial stone, extends the service life of the building materials system, and has environmental protection and economic advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462019A_ABST
    Figure CN119462019A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to an interface-enhanced environment-friendly artificial stone and a preparation method thereof. The interface-enhanced environment-friendly artificial stone is prepared from raw materials through compression molding and curing, and the raw materials comprise 25 wt%-31 wt% of mineralized aggregate with the particle size being 2.36 mm-4. 75 mm, 44 wt%-50 wt% of mineralized aggregate with the particle size being smaller than or equal to 1.18 mm, 13 wt%-19 wt% of an inorganic cementing material, 1.5 wt%-3.5 wt% of an inorganic auxiliary cementing material, 2.5 wt%-4.5 wt% of an organic cementing material, 0.5 wt%-1.5 wt% of an additive and 0.5 wt%-1.5 wt% of a water reducing agent. And water accounts for 0.5 wt%-1.5 wt%. The mineralized aggregate is prepared from waste cement concrete. According to the preparation method, mineralized aggregate with the particle size between 1.18 mm and 2.36 mm is removed, the binding power of the mineralized aggregate is increased, the interface-enhanced environment-friendly artificial stone with high strength is prepared, and falling of particles on the surface of the artificial stone can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an interface-enhanced environmentally friendly artificial stone and a preparation method thereof. Background Art

[0002] Artificial stone is one of the main materials for building decoration. It has been widely used because of its diverse colors and good processability. Artificial stone is mainly divided into two types: organic and inorganic. Organic artificial stone has a soft texture, poor performance at high and low temperatures, and is prone to deformation and aging. Compared with organic artificial stone, inorganic artificial stone has a wider range of applications, and its raw materials mainly include cement and quartz sand. However, due to the high demand for aggregate, the preparation of inorganic artificial stone consumes a lot of natural resources. At the same time, the production of cement also produces a lot of carbon dioxide, which has an adverse impact on the environment.

[0003] According to the development concept of green environmental protection, the raw materials of inorganic artificial stone should meet the requirements of sustainability and economy. Preparing waste cement concrete into recycled aggregate and micro powder of inorganic artificial stone can not only save natural resources, but also reduce CO 2 However, the recycled aggregates prepared from waste cement concrete will be covered with hardened mortar and have micro cracks during the crushing process. Their physical properties are often inferior to those of natural aggregates. In addition, the gelling activity of the recycled aggregates is low and the particle size distribution is uneven. To solve this problem, CO 2 Mineralization of waste cement concrete to improve the performance of recycled aggregate and micro powder and fix CO 2 .

[0004] As the main part of artificial stone materials, the aggregate system and bonding system account for more than 90% of the total mass of artificial stone materials. As the main force-bearing unit of artificial stone materials, the gradation design after aggregate selection has a great influence on the performance of artificial stone. It is generally believed that the gaps between coarse aggregates should be filled with fine aggregates, and the particle size of the fine aggregate filling the coarse gaps should be smaller than the minimum size of the gaps to avoid interference between aggregates.

[0005] The invention patent with application number 202210841036.7 provides an environmentally friendly artificial stone using full-size mineralized waste cement concrete, and the aggregate has a wide range of particle sizes, ranging from 4 to 120 meshes. However, the artificial stone prepared by this technical solution still has the problem of particle shedding. For example, during the preparation of artificial stone, particles will fall off when it is cut. After processing, particles will also fall off the surface of the artificial stone during use, resulting in depressions and potholes on the surface of the artificial stone, which in turn affects its performance.

[0006] Therefore, it is necessary to provide an interface-enhanced artificial stone to reduce particle shedding. Summary of the invention

[0007] 1. Technical issues to be resolved

[0008] In order to solve the problem of particle shedding on the surface of artificial stone, causing depressions and potholes in the prior art, the present invention provides an interface-enhanced environmentally friendly artificial stone and a preparation method thereof, which is expected to enhance the bonding force between aggregate particles and reduce particle shedding on the surface of artificial stone by discontinuous grading of aggregates.

[0009] (II) Technical solution

[0010] In order to achieve the above object, the main technical solutions adopted by the present invention include:

[0011] In a first aspect, the present invention provides an interface-enhanced environmentally friendly artificial stone, wherein the environmentally friendly artificial stone is made of raw materials through pressing, molding and curing, wherein the raw materials include 25wt%-31wt% of mineralized aggregates with a particle size of 2.36mm-4.75mm, 44wt%-50wt% of mineralized aggregates with a particle size of ≤1.18mm, 13wt%-19wt% of inorganic cementitious materials, 1.5wt%-3.5wt% of inorganic auxiliary cementitious materials, 2.5wt%-4.5wt% of organic binders, 0.5wt%-1.5wt% of admixtures, 0.5wt%-1.5wt% of water reducers, and 0.5wt%-1.5wt% of water;

[0012] The mineralized aggregate is prepared from waste cement concrete.

[0013] In the above-mentioned interface-enhanced environmentally friendly artificial stone, preferably, the inorganic gelling material is cement;

[0014] The inorganic auxiliary gelling material is a mixture of metakaolin and silica fume, wherein the mass ratio of metakaolin to silica fume is 1:3-3:1.

[0015] The interface-enhanced environmentally friendly artificial stone as described above, preferably, the organic binder is styrene-butadiene emulsion and / or methyl cellulose ether;

[0016] When the organic binder is a mixture of styrene butadiene emulsion and methyl cellulose ether, the mass ratio of the styrene butadiene emulsion to the methyl cellulose ether is 5:1-1:3.

[0017] The interface-enhanced environmentally friendly artificial stone as described above, preferably, the admixture is triethanolamine;

[0018] The water reducer is a polycarboxylic acid high-efficiency water reducer, and the solid content of the water reducer is 25-35%.

[0019] As described above, for the interface-enhanced environmentally friendly artificial stone, preferably, in the raw materials of the environmentally friendly artificial stone, the mineralized aggregate accounts for 70wt%-76wt% of the raw materials.

[0020] In a second aspect, the present invention further provides a method for preparing the above-mentioned interface-enhanced environmentally friendly artificial stone, comprising the following steps:

[0021] S1: Mix mineralized aggregates of two specifications, one with a particle size of 2.36 mm to 4.75 mm and one with a particle size of ≤1.18 mm, an inorganic cementitious material, an inorganic auxiliary cementitious material, an organic binder, an admixture, and water to obtain a mixed material;

[0022] S2: Pressing and molding the mixed material to obtain a blank;

[0023] S3: Curing the blank to obtain artificial stone.

[0024] In the method for preparing the interface-enhanced environmentally friendly artificial stone as described above, preferably, in step S1, the method for preparing the mineralized aggregate comprises the following steps:

[0025] A1: crushing and screening the waste cement concrete to obtain recycled aggregate; the particle size range of the recycled aggregate includes two intervals: 2.36mm-4.75mm and ≤1.18mm;

[0026] A2: Place the recycled aggregate in a soluble magnesium salt solution and introduce CO into the soluble magnesium salt solution. 2 , the recycled aggregate is subjected to wet mineralization treatment to obtain mineralized aggregate.

[0027] In the method for preparing the interface-enhanced environmentally friendly artificial stone as described above, preferably, in step A2:

[0028] In soluble magnesium salt solution, Mg 2+ The concentration is 0.1-0.3 mol / L;

[0029] The mass volume ratio w:v of recycled aggregate with a particle size range of 2.36mm-4.75mm or recycled aggregate with a particle size ≤1.18mm and soluble magnesium salt solution is 1g:(10-25)ml;

[0030] For every 100 ml of soluble magnesium salt solution, CO 2 The inlet flow rate is 0.08-0.2L / min;

[0031] The temperature of the wet mineralization treatment is 75-85°C, and the time of the wet mineralization treatment is 5-10 minutes.

[0032] In the method for preparing the above-mentioned interface-enhanced environmentally friendly artificial stone, preferably, in step S2, the pressing pressure is 2×10 5 -2.5×10 5 N, the pressing time is 28-32s.

[0033] In the method for preparing the interface-enhanced environmentally friendly artificial stone as described above, preferably, in step S3, the curing temperature is 23-27° C., the curing humidity is 35-45%, and the curing time is ≥ 7 days.

[0034] (III) Beneficial effects

[0035] First, the present invention uses mineralized aggregates obtained by mineralizing waste cement concrete as artificial stone aggregates, selects appropriate discontinuous grading, eliminates mineralized aggregates with particle sizes between 1.18 mm and 2.36 mm, increases the bonding force of mineralized aggregates through discontinuous grading, strengthens the interface performance between mineralized aggregates and cementitious materials, prepares high-strength interface-enhanced environmentally friendly artificial stones, and can avoid the phenomenon of surface particle shedding during the cutting production and use of artificial stones.

[0036] Second, the present invention utilizes the high alkalinity of the hydration products of waste cement concrete to make CO 2 Ca(OH) in waste cement concrete 2 Formation of CaCO 3 and H 2 O, obtain mineralized aggregate, can reduce the amount of inorganic cementitious materials used, and at the same time prepare environmentally friendly artificial stone with carbon fixation effect, which is beneficial to extend the service life of the building material system.

[0037] Third, the mineralized aggregate in the raw materials of the artificial stone in the present invention comes from waste cement concrete, which has a wide source of raw materials. The waste concrete can be disposed of, which reduces accumulation and land occupation, greatly reduces the demand for natural stone mining, and has important environmental protection significance. Moreover, when the mineralized aggregate is processed from waste concrete, the processing is simple and the price is low, which is convenient for wide application. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic diagram of the preparation process of the interface enhanced environmentally friendly artificial stone in the present invention. DETAILED DESCRIPTION

[0039] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below in conjunction with the accompanying drawings and specific implementation methods.

[0040] In the prior art solution with application number 202210841036.7, the aggregate particle size range is relatively wide, which meets the general rule of using fine aggregate to fill the gaps between coarse aggregates. However, the artificial stone of this technical solution still has the problem of particle shedding. After long-term research and experiments, the researchers of this application found that for aggregates with a particle size range of ≤4.75mm, if the components with a particle size of 1.18mm-2.36mm are removed, the problem of particle shedding of artificial stone can be reduced. Based on the above research findings, the present invention provides an interface-enhanced environmentally friendly artificial stone, which is made of raw materials through pressing, molding and curing. Among the raw materials, mineralized aggregates with a particle size of 2.36mm-4.75mm account for 25wt%-31wt%, mineralized aggregates with a particle size ≤1.18mm account for 44wt%-50wt%, inorganic cementitious materials account for 13wt%-19wt%, inorganic auxiliary cementitious materials account for 1.5wt%-3.5wt%, organic binders account for 2.5wt%-4.5wt%, admixtures account for 0.5wt%-1.5wt%, water reducers account for 0.5wt%-1.5wt%, and water accounts for 0.5wt%-1.5wt%.

[0041] In the present invention, the mineralized aggregate is prepared from waste cement concrete.

[0042] As a preference, the mineralized aggregate (the sum of the two particle size ranges) accounts for 70wt%-76wt% of the raw materials of the environmentally friendly artificial stone.

[0043] Preferably, the inorganic cementitious material in the present invention is cement, more preferably PO52.5 cement. The inorganic auxiliary cementitious material is preferably a mixture of metakaolin and silica fume, wherein the mass ratio of metakaolin to silica fume is 1:3-3:1, more preferably 1:1.

[0044] Preferably, the organic binder in the present invention is styrene butadiene emulsion and / or methyl cellulose ether. When the organic binder is a mixture of styrene butadiene emulsion and methyl cellulose ether, the mass ratio of styrene butadiene emulsion to methyl cellulose ether is 5:1-1:3, preferably 4:1.

[0045] Preferably, the admixture in the present invention is triethanolamine, the water reducer is a polycarboxylic acid high-efficiency water reducer, and the solid content of the water reducer is 25-35%, preferably 30%.

[0046] The present invention uses mineralized aggregate obtained by mineralizing waste cement concrete as artificial stone aggregate, selects appropriate discontinuous grading, and eliminates mineralized aggregate with a particle size greater than 1.18 mm and less than 2.36 mm. The discontinuous grading increases the bonding force of the mineralized aggregate, strengthens the interface performance between the mineralized aggregate and the cementitious material, and prepares an environmentally friendly artificial stone with high strength and interface enhancement. Compared with the prior art, the discontinuous grading of the mineralized aggregate of the present invention can avoid the phenomenon of surface particle shedding during the cutting production and use of the artificial stone.

[0047] The present invention utilizes the high alkalinity of waste cement concrete hydration products and uses mineralization treatment to make CO 2 Ca(OH) in waste cement concrete 2 Formation of CaCO 3 and H 2 O, obtain mineralized aggregate, can reduce the amount of inorganic cementitious materials used, and at the same time prepare environmentally friendly artificial stone with carbon fixation effect, which is beneficial to extend the service life of the building material system.

[0048] In addition, the mineralized aggregate in the raw materials of the artificial stone in the present invention comes from waste cement concrete, which has a wide source of raw materials. The waste concrete can be disposed of, which reduces accumulation and land occupation, greatly reduces the demand for natural stone mining, and has important environmental protection significance. Moreover, when the mineralized aggregate is processed from waste concrete, the processing is simple and the price is low, which is convenient for wide application.

[0049] like Figure 1 As shown, the present invention also provides a method for preparing the above-mentioned interface enhanced environmentally friendly artificial stone, comprising the following steps:

[0050] S1: Mix mineralized aggregate with a particle size of 2.36mm-4.75mm, mineralized aggregate with a particle size of ≤1.18mm, inorganic cementitious material, inorganic auxiliary cementitious material, organic binder, admixture, and water to obtain a mixed material. Specifically, in this step, the mineralized aggregate with a particle size of 2.36mm-4.75mm accounts for 25wt%-31wt% of the raw materials, the mineralized aggregate with a particle size of ≤1.18mm accounts for 44wt%-50wt% of the raw materials, the inorganic cementitious material accounts for 13wt%-19wt% of the raw materials, the inorganic auxiliary cementitious material accounts for 1.5wt%-3.5wt% of the raw materials, the organic binder accounts for 2.5wt%-4.5wt% of the raw materials, the admixture accounts for 0.5wt%-1.5wt% of the raw materials, the water reducer accounts for 0.5wt%-1.5wt%, and the water accounts for 0.5wt%-1.5wt% of the raw materials.

[0051] S2: The mixed material is subjected to compression molding to obtain a blank.

[0052] S3: Curing the blank to obtain artificial stone.

[0053] Preferably, in the above step S1, the method for preparing the mineralized aggregate comprises the following steps:

[0054] A1: The waste cement concrete (waste concrete) is crushed and screened to remove aggregates with a particle size greater than 1.18 mm and less than 2.36 mm (removing powder) to obtain recycled aggregate. The particle size range of the recycled aggregate obtained by screening in this step includes two intervals: 2.36 mm-4.75 mm and ≤1.18 mm.

[0055] A2: Place the recycled aggregate in a soluble magnesium salt solution and introduce CO into the soluble magnesium salt solution. 2 , the recycled aggregate is subjected to wet mineralization treatment to obtain mineralized aggregate. Specifically, the recycled aggregate with a particle size of 2.36 mm-4.75 mm and the recycled aggregate with a particle size of ≤1.18 mm can be subjected to wet mineralization treatment to obtain mineralized aggregates with different particle size ranges, and then the mineralized aggregate with a particle size of 2.36 mm-4.75 mm and the mineralized aggregate with a particle size of ≤1.18 mm are dry mixed. In this step, the solute in the soluble magnesium salt solution is preferably MgCl 2 Mg(NO 3 ) 2 etc.Mg 2+ The concentration is 0.1-0.3 mol / L, preferably 0.2 mol / L. The mass volume ratio w:v of the recycled aggregate with a particle size range of 2.36 mm-4.75 mm or a recycled aggregate with a particle size ≤1.18 mm and the soluble magnesium salt solution is 1 g:(10-25) ml, preferably 1 g:20 ml. In every 100 ml of the soluble magnesium salt solution, CO 2 The inlet flow rate is 0.08-0.2 L / min, preferably 0.1 L / min, and CO 2 The concentration is preferably 100%. In the present invention, the temperature of the wet mineralization treatment is 75-85°C, and the time of the wet mineralization treatment is 5-10 minutes.

[0056] In the above wet mineralization process, Mg 2+ It will react with the recycled aggregate to form a stable brucite system, and then the brucite will dissolve again and turn into Mg 2+ Therefore, Mg 2+ It can be regarded as a catalyst in the wet mineralization reaction. The wet carbonization (mineralization) can be regarded as a non-steady-state catalytic reaction, which can accelerate the efficiency of the mineralization reaction. The mineralized aggregate can be prepared in just 5-10 minutes. In addition, compared with the prior art, the present invention uses Mg to react with carbon dioxide to generate calcium carbonate to achieve carbon fixation. 2+As a catalyst for wet mineralization, CO 2 Ca(OH) in waste cement concrete 2 The generated CaCO 3 It has a unique crystal form, a unique fibrous structure, significantly improved compressive strength, and has a higher modulus, hardness, and lower water absorption.

[0057] In the present invention, the waste cement concrete can be crushed and screened only once to obtain the recycled aggregate, and the recycled aggregate is subjected to wet mineralization treatment, which can not only absorb CO in a short time, but also 2 , improve the low density and porosity of recycled aggregate, repair the micro cracks generated during the crushing process, improve the compressive strength, hardness and elastic modulus of artificial stone, and reduce water absorption. The interface performance between aggregate and cement after wet mineralization treatment is further strengthened.

[0058] Preferably, in the above step S2, the pressure of the pressing molding is 2×10 5 -2.5×10 5 N, the time of compression molding is 28-32s. Specifically, the raw materials mixed evenly in step S1 are placed in a molding mold, and a blank is formed by static compression molding in a press, and there is no need for vacuuming and vibration molding. Furthermore, the present invention does not require a film to protect the surface of the artificial stone during the pressing process, and can be demolded immediately after molding.

[0059] Preferably, in the above step S3, the blank is placed in a curing room and cured at 23-27° C. and 35-45% humidity. The curing process does not require humidification or pressurization. The curing time is ≥ 7 days, and the interface-enhanced environmentally friendly artificial stone can be obtained.

[0060] The artificial stone of the present invention has low cost. The aggregate of the artificial stone is 100% mineralized aggregate. The wet mineralization method is used to absorb a large amount of CO 2 The quality of aggregates is improved, and aggregates of certain particle sizes are eliminated through discontinuous grading, thereby improving the dosage of the cementitious system, and preparing high-strength interface-enhanced environmentally friendly artificial stone. The artificial stone will not fall off during the cutting process, and has good application prospects in building materials.

[0061] In order to further clarify the scheme of the present invention and its technical advancement, the following is a description in conjunction with specific embodiments and technical effects.

[0062] Example 1

[0063] This embodiment provides a method for preparing an interface-enhanced environmentally friendly artificial stone, comprising the following steps:

[0064] S1: Crushing and screening the waste cement concrete to obtain recycled aggregate with a particle size of 2.36mm-4.75mm and recycled aggregate with a particle size of ≤1.18mm. The two recycled aggregates were placed in a 0.2mol / L MgCl 2 In the solution, CO is introduced into the system 2 , wet mineralization treatment for 7 minutes to obtain mineralized aggregate. In this step, the recycled aggregate and MgCl 2 The mass volume ratio of the solution is 1g:20ml, CO 2 The flow rate is 0.1L / min / 100ml, and the CO 2 The concentration is 100%.

[0065] S2: The mineralized aggregate prepared in step S1, PO52.5 cement, inorganic auxiliary cementitious material composed of metakaolin and silica fume, organic cementitious material composed of styrene butadiene emulsion and methyl cellulose ether, water, triethanolamine and polycarboxylic acid high-efficiency water reducing agent are mixed and stirred to obtain a mixed material. The mass ratio of metakaolin to silica fume is 1:1, and the mass ratio of styrene butadiene emulsion to methyl cellulose ether is 4:1.

[0066] The mixed material in this step includes 26wt% of mineralized aggregate with a particle size of 2.36mm-4.75mm, 48wt% of mineralized aggregate with a particle size ≤1.18mm, 17wt% of PO52.5 cement, 2.5wt% of inorganic auxiliary cementitious material, 3.5wt% of organic binder, 1wt% of triethanolamine, 1wt% of polycarboxylic acid high-efficiency water reducer, and 1wt% of water.

[0067] S3: Put the mixed material into the mold and 5 The material was statically pressed for 31 seconds under a constant pressure of N, and demolded to obtain a blank. The blank was placed in a curing room with a temperature of 23° C. and a humidity of 40% for curing. After 7 days, the blank was cured to obtain an artificial stone.

[0068] Example 2

[0069] This embodiment provides a method for preparing an interface-enhanced environmentally friendly artificial stone, comprising the following steps:

[0070] S1: Crushing and screening the waste cement concrete to obtain recycled aggregate with a particle size of 2.36mm-4.75mm and recycled aggregate with a particle size of ≤1.18mm. The two recycled aggregates were placed in a 0.3mol / L MgCl 2 In the solution, CO is introduced into the system 2 , wet mineralization treatment for 5 minutes to obtain mineralized aggregate. In this step, the recycled aggregate and MgCl 2The mass volume ratio of the solution is 1g:25ml, CO 2 The flow rate is 0.2L / min / 100ml, and the CO 2 The concentration is 100%.

[0071] S2: Mix the mineralized aggregate prepared in step S1, PO52.5 cement, inorganic auxiliary cementitious material composed of metakaolin and silica fume, styrene-butadiene emulsion, water, triethanolamine and polycarboxylic acid high-efficiency water reducing agent, and stir evenly to obtain a mixed material, wherein the mass ratio of metakaolin to silica fume is 1:3.

[0072] The mixed material in this step includes 28wt% of mineralized aggregate with a particle size of 2.36mm-4.75mm, 47wt% of mineralized aggregate with a particle size ≤1.18mm, 16.1wt% of PO52.5 cement, 2.5wt% of inorganic auxiliary cementitious material, 3.5wt% of styrene-butadiene emulsion, 0.9wt% of triethanolamine, 1wt% of polycarboxylic acid high-efficiency water reducer, and 1wt% of water.

[0073] S3: Put the mixed material into the mold and 5 The material was statically pressed for 30 seconds under a constant pressure of N, and demolded to obtain a blank. The blank was placed in a curing room at a temperature of 25° C. and a humidity of 40% for curing. After 7 days, the blank was cured to obtain an artificial stone.

[0074] Example 3

[0075] This embodiment provides a method for preparing an interface-enhanced environmentally friendly artificial stone, comprising the following steps:

[0076] S1: Crushing and screening the waste cement concrete to obtain recycled aggregate with a particle size of 2.36mm-4.75mm and recycled aggregate with a particle size of ≤1.18mm. The two recycled aggregates were placed in a 0.1mol / L MgCl 2 In the solution, CO is introduced into the system 2 , wet mineralization treatment for 10 minutes to obtain mineralized aggregate. In this step, the recycled aggregate and MgCl 2 The mass volume ratio of the solution is 1g:10ml, CO 2 The flow rate is 0.08L / min / 100ml, and the CO 2 The concentration is 100%.

[0077] S2: Mix the mineralized aggregate prepared in step S1, PO52.5 cement, inorganic auxiliary cementitious material composed of metakaolin and silica fume, methyl cellulose ether, water, triethanolamine and polycarboxylic acid high-efficiency water reducing agent, and stir evenly to obtain a mixed material, wherein the mass ratio of metakaolin to silica fume is 3:1.

[0078] The mixed material in this step includes 30wt% of mineralized aggregate with a particle size of 2.36mm-4.75mm, 44wt% of mineralized aggregate with a particle size ≤1.18mm, 16.8wt% of PO52.5 cement, 2.5wt% of inorganic auxiliary cementitious material, 3.5wt% of methyl cellulose ether, 1.2wt% of triethanolamine, 1wt% of polycarboxylic acid high-efficiency water reducer, and 1wt% of water.

[0079] S3: Put the mixed material into the mold and 5 The material was statically pressed under a constant pressure of N for 29 seconds, and demolded to obtain a blank. The blank was placed in a curing room at a temperature of 27° C. and a humidity of 45% for curing. After 7 days, the blank was cured to obtain an artificial stone.

[0080] Comparative Example 1

[0081] This comparative example provides a method for preparing an environmentally friendly artificial stone, which is different from Example 1 in that the recycled aggregate in step S1 is not subjected to wet mineralization treatment.

[0082] Comparative Example 2

[0083] This comparative example provides a method for preparing an environmentally friendly artificial stone, which differs from Example 1 in that:

[0084] In step S1, the waste cement concrete is crushed and sieved to obtain recycled aggregate with a particle size of 2.36 mm-4.75 mm, recycled aggregate with a particle size greater than 1.18 mm and less than 2.36 mm, and recycled aggregate with a particle size ≤1.18 mm.

[0085] The mixed material in step S2 includes 21wt% of mineralized aggregate with a particle size of 2.36mm-4.75mm, 43wt% of mineralized aggregate with a particle size of ≤1.18mm, and 10wt% of recycled aggregate with a particle size of greater than 1.18mm and less than 2.36mm.

[0086] The physical properties of the artificial stones prepared in Examples 1-3 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.

[0087] Table 1 Statistical table of physical properties of artificial stones prepared in Examples 1-3 and Comparative Examples 1-2

[0088]

[0089] As shown in Table 1, the compressive strength, hardness, elastic modulus and water absorption of the interface-enhanced environmentally friendly artificial stone prepared by the present invention are significantly better than those of Comparative Example 1. The present invention enhances the adhesion between aggregate particles and enhances the interface strength of the artificial stone by discontinuous grading of the aggregate. In addition, the present invention uses magnesium ions as a catalyst to perform wet mineralization on the recycled aggregate, which can significantly improve the compressive strength, hardness and elastic modulus of the artificial stone, and reduce the water absorption. The interface between the aggregate and cement treated by wet mineralization can be further enhanced.

[0090] The artificial stones prepared in Examples 1-3 and Comparative Examples 1-2 were cut. After observation and statistics, there was no particle shedding in Examples 1-3 and Comparative Example 1. After the artificial stone in Comparative Example 2 was cut, there were obvious depressions on the cut surface and obvious particle shedding.

[0091] Therefore, the present invention adopts reasonable discontinuous grading, first fixes carbon through aggregate, and then makes artificial stone, which reduces the use of natural stone and absorbs CO 2 Under such circumstances, the compressive strength of the prepared interface-enhanced environmentally friendly artificial stone is greatly improved, and the artificial stone will not fall off during the cutting process, and has good application prospects in building materials.

[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An interface-enhanced environmentally friendly artificial stone, characterized in that: The environmentally friendly artificial stone is made of raw materials through pressing, molding and curing. Among the raw materials, mineralized aggregates with a particle size of 2.36 mm-4.75 mm account for 25 wt%-31 wt%, mineralized aggregates with a particle size of ≤1.18 mm account for 44 wt%-50 wt%, inorganic cementitious materials account for 13 wt%-19 wt%, inorganic auxiliary cementitious materials account for 1.5 wt%-3.5 wt%, organic binders account for 2.5 wt%-4.5 wt%, admixtures account for 0.5 wt%-1.5 wt%, water reducers account for 0.5 wt%-1.5 wt%, and water accounts for 0.5 wt%-1.5 wt%; The mineralized aggregate is prepared from waste cement concrete.

2. The interface-enhanced environmentally friendly artificial stone according to claim 1, characterized in that: The inorganic gelling material is cement; The inorganic auxiliary gelling material is a mixture of metakaolin and silica fume, wherein the mass ratio of metakaolin to silica fume is 1:3-3:

1.

3. The interface-enhanced environmentally friendly artificial stone according to claim 1, characterized in that: The organic binder is styrene-butadiene emulsion and / or methyl cellulose ether; When the organic binder is a mixture of styrene butadiene emulsion and methyl cellulose ether, the mass ratio of the styrene butadiene emulsion to the methyl cellulose ether is 5:1-1:

3.

4. The interface-enhanced environmentally friendly artificial stone according to claim 1, characterized in that: The additive is triethanolamine; The water reducer is a polycarboxylic acid high-efficiency water reducer, and the solid content of the water reducer is 25-35%.

5. The interface-enhanced environmentally friendly artificial stone according to claim 1, characterized in that: Among the raw materials of the environmentally friendly artificial stone, the mineralized aggregate accounts for 70wt%-76wt% of the raw materials.

6. A method for preparing the interface-enhanced environmentally friendly artificial stone according to any one of claims 1 to 5, characterized in that: The steps include: S1: Evenly mix two kinds of mineralized aggregates with a particle size of 2.36 mm-4.75 mm and a particle size of ≤1.18 mm, an inorganic cementitious material, an inorganic auxiliary cementitious material, an organic binder, an admixture, and water to obtain a mixed material; S2: Pressing and molding the mixed material to obtain a blank; S3: Curing the blank to obtain artificial stone.

7. The method for preparing the interface-enhanced environmentally friendly artificial stone according to claim 6, characterized in that: In step S1, the method for preparing mineralized aggregate comprises the following steps: A1: crushing and screening the waste cement concrete to obtain recycled aggregate; the particle size range of the recycled aggregate includes two intervals: 2.36mm-4.75mm and ≤1.18mm; A2: The recycled aggregate is placed in a soluble magnesium salt solution, and CO2 is introduced into the soluble magnesium salt solution to perform a wet mineralization treatment on the recycled aggregate to obtain a mineralized aggregate.

8. The method for preparing the interface-enhanced environmentally friendly artificial stone according to claim 7, characterized in that: In step A2: In soluble magnesium salt solution, Mg 2+ The concentration is 0.1-0.3 mol / L; The mass volume ratio w:v of recycled aggregate with a particle size range of 2.36mm-4.75mm or recycled aggregate with a particle size ≤1.18mm and soluble magnesium salt solution is 1g:(10-25)ml; For every 100 ml of soluble magnesium salt solution, the flow rate of CO2 is 0.08-0.2 L / min; The temperature of the wet mineralization treatment is 75-85°C, and the time of the wet mineralization treatment is 5-10 minutes.

9. The method for preparing the interface-enhanced environmentally friendly artificial stone according to claim 6, characterized in that: In step S2, the pressing pressure is 2×10 5 -2.5×10 5 N, the pressing time is 28-32s.

10. The method for preparing the interface-enhanced environmentally friendly artificial stone according to claim 6, characterized in that: In step S3, the curing temperature is 23-27° C., the curing humidity is 35-45%, and the curing time is ≥ 7 days.

Citation Information

Patent Citations

  • Environmentally friendly artificial stone utilizing fully mineralized waste cement concrete and its preparation method

    CN115286307B